Subunit structure of the variable V-1 antigen of Mycoplasma pulmonis. - Watson, H. L. (1989)
It was previously shown that multiple structural variants of the V-1 antigen (variable antigen 1) of Mycoplasma pulmonis could be found within a single strain. This antigen is unusual in that it produces a ladder pattern after sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis. The present study showed that some variants of V-1 could be extracted into the aqueous phase of a phenol-H2O system. Analysis with anti-V-1 monoclonal antibodies showed that the phenol-H2O-extracted V-1 had a regular spacing of 3.1 kilodaltons (kDa) between bands and trypsinization of this extracted V-1 resulted in the gradual symmetrical collapse (2.9-kDa increments) of the ladder into a single band, suggesting the presence of multiple identical subunits within the V-1 structure. The upper band from the phenol-H2O-extracted V-1 was isolated and analyzed by SDS-polyacrylamide gel electrophoresis immunoblotting, resulting in the regeneration of the original ladder pattern with 3.1-kDa spacing between bands. When V-1 was boiled for increasing times in the presence of SDS, the staining intensity of the upper band decreased with the concurrent appearance of additional lower-molecular-weight bands. Finally, by using whole cells, it was found that the lower-molecular-weight species of the ladder pattern selectively partitioned into the hydrophobic phase of a Triton X-114 phase partitioning system, and the higher-molecular-weight bands were found in the aqueous phase. These data indicate that the V-1 bands are composed of subunits which may aggregate via hydrophobic interactions and that these aggregates at least partially dissociate when exposed to harsh denaturing conditions, resulting in the characteristic ladder pattern of V-1.